2021
DOI: 10.3389/fneur.2020.616661
|View full text |Cite
|
Sign up to set email alerts
|

Recovery From Repeat Mild Traumatic Brain Injury in Adolescent Rats Is Dependent on Pre-injury Activity State

Abstract: Adolescents and young adults have the highest incidence of mild traumatic brain injury (mTBI); sport-related activities are a major contributor. Roughly a third of these patients diagnosed with mTBI are estimated to have received a subsequent repeat mTBI (rTBI). Previously, animal studies have only modeled mTBI in sedentary animals. This study utilizes physical activity as a dependent variable prior to rTBI in adolescent rats by allowing voluntary exercise in males, establishing the rat athlete (rathlete). Rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…In exercise addiction, an individual develops an obsession with exercise causing features such as withdrawal symptoms and mood modification (Peluso & Guerra de Andrade, 2005;Weinstein et al, 2015). Although previous studies in rats have used different methods of reporting distance run or number of wheel revolutions over different time periods (Fan et al, 2022;Ferguson et al, 2020;Ferguson et al, 2021;Ishikawa et al, 2014;, the amount of exercise experienced by the rats in our study generally appears high by comparison. This may be a possible explanation for the increase in anxiety-and depressionlike behaviors seen in our exercise rats.…”
Section: Duration and Severity Of Exercisementioning
confidence: 67%
“…In exercise addiction, an individual develops an obsession with exercise causing features such as withdrawal symptoms and mood modification (Peluso & Guerra de Andrade, 2005;Weinstein et al, 2015). Although previous studies in rats have used different methods of reporting distance run or number of wheel revolutions over different time periods (Fan et al, 2022;Ferguson et al, 2020;Ferguson et al, 2021;Ishikawa et al, 2014;, the amount of exercise experienced by the rats in our study generally appears high by comparison. This may be a possible explanation for the increase in anxiety-and depressionlike behaviors seen in our exercise rats.…”
Section: Duration and Severity Of Exercisementioning
confidence: 67%
“…It would be interesting to determine if the correlations with the hippocampus are specifically due to exercise and rathletes in this study and if it relates to exerciseinduced neuroplasticity and neuroprotection following a brain insult. Previously, we have shown a significant increase in PGC1α in the hippocampus and parietal cortex in adolescent male rathletes after 20 days of voluntary wheel running with protection against cognitive deficits following brain injury (28). Similarly, another study allowing juvenile rats 20 days of voluntary exercise found that gene expression of PGC1α was only increased in the hippocampus of exercised females, and was actually decreased in the prefrontal cortex of males (29).…”
Section: Discussionmentioning
confidence: 79%
“…One unexpected result of this study was that levels of BDNF in the parietal cortex and the hippocampus were similar for running and sedentary rats and may be due to age of the rats or length of exercise regimen. Exercise has been shown to serve as a neuroprotectant for brain injury, preventing memory dysfunction, through the upregulation of BDNF (28). Previous studies of juvenile male and female rats found a significant increase in gene expression of BDNF in the hippocampus but not parietal cortex following 20 days of voluntary wheel running (29).…”
Section: Discussionmentioning
confidence: 99%
“…Several pre-clinical neurotrauma studies have subsequently incorporated measures of social behavior into their study designs, considering how social functioning may be altered after injuries sustained across a lifespan (29)(30)(31). The three-chamber social approach test, and/or the classical resident-intruder paradigm, are the most commonly used and appear to be the most robust for both mice and rats.…”
Section: Experimental Models Of Social Behavior Impairments After Tbimentioning
confidence: 99%